Legal Challenges in the Development of Information and Communication Technology SMEs in Jabodetabek Region, Indonesia - Ujang Badru Jaman; Arief Fahmi Lubis; Muhamad Sigid Safarudin; Suhartono Suhartono (Westscience Press, 2023)
The Jabodetabek region of Indonesia has had notable growth in the Information and Communication Technology (ICT) sector, primarily due to the efforts of Small and Medium-sized Enterprises (SMEs). SMEs encounter a complex network of legal obstacles that impede their growth and ability to compete. Using a mixed-methods approach that includes both quantitative surveys and qualitative interviews, this study explores these issues. The findings draw attention to important legal difficulties, such as limited access to legal services, contract conflicts, cybersecurity concerns, intellectual property issues, and regulatory compliance. The competitiveness and development of SMEs are significantly impacted by these issues. Comprehensive legal and legislative changes are advised to address these problems. These include simplified rules, strict enforcement of intellectual property rights, effective dispute resolution procedures, cybersecurity assistance, and improved access to legal services. This study highlights the significance of a supportive legal framework for innovation and economic growth, adding to our understanding of the legal aspects of ICT SME development in Jabodetabek.